Absence of prostate oedema obviates the need for delay between fiducial marker insertion and radiotherapy simulation. Issue 4 (2nd July 2020) - Patel, Deepti; Tan, Alex; Brown, Amy; Pain, Tilley
Abstract: Introduction: Fiducial markers (FMs) are commonly inserted into the prostate for image guided radiation therapy. This study aimed to quantify prostate oedema immediately following FM insertion compared to prostate volumes measured a week later, at the time of simulation for radiation therapy. Methods: Thirty patients underwent a verification computed tomography (VCT) scan in treatment position immediately after the fiducial insertion and their planning computed tomography scan (PCT) one week after. Patient data sets were retrospectively evaluated, comparing prostate volumes and planning target volumes (PTV). Volumes were delineated by a single radiation oncologist, blinded to whether the scan was VCT or PCT. Distances between the FMs were measured on both scans. Descriptive statistics described the data, DICE similarity co‐efficient (DSC) calculated, and paired t‐tests were used to compare paired data. Results: The median prostate volume was 35.09 cc and 36.31 cc for VCT and PCT data sets, respectively, and median PTV was 118.56 cc and 127.04 cc for VCT and PCT, respectively. There was no significant difference in prostate volumes ( P  = 0.3037) or PTV ( P  = 0.1279), with a DSC of 0.87 (range 0.76–0.91) and 0.91 (range 0.85 to 0.95), respectively. Similarly, there was no significant difference in distance between fiducial markers ( P  > 0.05). Conclusion: This study demonstrates no statistically significant difference in prostate or PTV volumes ( P  > 0.05) between the CT acquired at fiducial marker insertion compared with the CT acquired a week later. Therefore, oedema is not significant enough to justify a delay between FM insertion and simulation. Abstract : This study demonstrates no statistically significant difference in prostate or planning target volumes ( P  > 0.05) between the CT acquired at fiducial marker (FM) insertion compared with the CT acquired a week later. Therefore, oedema is not significant enough to justify a delay between FM insertion and simulation.